A Quadruplex qPCR for Detection and Differentiation of Classic and Natural Recombinant Myxoma Virus Strains of Leporids - Fábio A. Abade dos Santos (MDPI AG, 2021)
A natural recombinant myxoma virus (referred to as ha-MYXV or MYXV-Tol08/18) emerged in the Iberian hare (Lepus granatensis) and the European rabbit (Oryctolagus cuniculus) in late 2018 and mid-2020, respectively. This new virus is genetically distinct from classic myxoma virus (MYXV) strains that caused myxomatosis in rabbits until then, by acquiring an additional 2.8 Kbp insert within the m009L gene that disrupted it into ORFs m009L-a and m009L-b. To distinguish ha-MYXV from classic MYXV strains, we developed a robust qPCR multiplex technique that combines the amplification of the m000.5L/R duplicated gene, conserved in all myxoma virus strains including ha-MYXV, with the amplification of two other genes targeted by the real-time PCR systems designed during this study, specific either for classic MYXV or ha-MYXV strains. The first system targets the boundaries between ORFs m009L-a and m009L-b, only contiguous in classic strains, while the second amplifies a fragment within gene m060L, only present in recombinant MYXV strains. All amplification reactions were validated and normalized by a fourth PCR system directed to a housekeeping gene (18S rRNA) conserved in eukaryotic organisms, including hares and rabbits. The multiplex PCR (mPCR) technique described here was optimized for Taqman® and Evagreen® systems allowing the detection of as few as nine copies of viral DNA in the sample with an efficiency > 93%. This real-time multiplex is the first fast method available for the differential diagnosis between classic and recombinant MYXV strains, also allowing the detection of co-infections. The system proves to be an essential and effective tool for monitoring the geographical spread of ha-MYXV in the hare and wild rabbit populations, supporting the management of both species in the field.